Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

2 tan^-1(tan x/2 tan y/2)= cos^-1( cos x + cos y / 1+ cos x cos y)

2 tan^-1(tan x/2 tan y/2)= cos^-1( cos x + cos y / 1+ cos x cos y)

Grade:12

1 Answers

Arun
25763 Points
3 years ago
Dear student
 

We have,

sinA + sin2A = 1   ...(1) 

⇒ sinA = – sin2A   ...(2)

Now

cos2+ cos4

= (– sin2A) + {(1 – sin2A)}2

= sinA + sin2[from (2)]  

= 1 [from (1)]

 

Regards

Arun (askIITians forum expert)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free